Strategic Optimization in Distribution Centers: Leveraging Relocation, P-Median, and GIS-Based Routing for Enhanced Efficiency - Liperda, Rahmad Inca; Rachmawati, Nur Layli; Ruswandi, Nanda; Apriani, Ayu; Amarajaya, Delinda; Nurdiana; Tsabittaah, Rifdah (UNIPA PRESS, 2024)
In the realm of B2C (Business to Customer) company marketing, it is imperative to focus on sales and customer satisfaction. To uphold customer contentment, B2C enterprises must strategically position their delivery facilities to optimize efficiency and minimize both time and operational expenditures. PT ABC, a B2C entity specializing in the distribution of packaged goods, currently faces challenges in handling a substantial volume of requests, some of which are situated far from their distribution centers. This predicament leads to elevated fulfillment costs and an inefficient operational process. Consequently, the relocation of distribution center facilities becomes a necessity. The relocation process will be executed employing the P-Median method, facilitated by LINGO software. The P-Median analysis yielded three potential new locations: Cikupa, Jombang Wetan, and Bencongan Indah. Subsequently, further assessment through the resolution of the MTCVRP (Multitrip Capacitated Vehicle Routing Problem) with the aid of ArcGIS software was conducted. As a result, Jombang Wetan emerged as the optimal candidate, exhibiting a remarkable reduction of 165.7 kilometers or a 31.33% decrease in average mileage. This choice promises a more efficient and effective product distribution operation.